Development and performance of perovskites as a cathode with application towards gas cleaning: article - Sabudin, Laila Azwani; Mohd Akhir, Ammar (2019)
The solid oxide fuel cell (SOFCs) is a new alternative energy and environmentally friendly. There are three major elements in SOFC which are anode, cathode and electrolyte. As perovskite is one of the major materials in SOFC where used as a cathode. However, the development of high-quality performance SOFC might be facing a difficulty because of its development quite costly. This study is to determine the electrical conductivity of cathode achieved and to abricate SOFC cathode using combination of polyvinyl alcohol as a binder and starch. During this study, three different weight percentage of starch is used to determine the electrical conductivity. The result showed all the samples are classified as crystallite thus can use Scherrer equation to calculated the average crystallite size. The average crystallite sizes are decreasing as the starch weight percentage increase. For conductivity test, there is unavoidable error during the test. The conductivity of LSCF pellet should be increase as the weight percentage of starch increase. The result showed fluctuation resulting from the catalytic activity for oxygen reduction of LSCF cathode reaction. Thus, the objectives of this study not fully achieved due the unavoidable error lead to fluctuation result.